NILAI TAMBAH DAN HARGA POKOK PRODUKSI SOSIS GULUNG DI CV CUCURUTUKU CERIA BANDAR LAMPUNG - Nidya Oktaviani; Wuryaningsih Dwi Sayekti; Indah Listiana (Lampung University, 2021)
This research aims to analyze the added value, the amount of production cost and selling cost of sausage rolls. The method used in this research is case study. The location is chosen purposively at CV Cucurutuku Ceria in Bandar Lampung with consideration that CV Cucurutuku Ceria trading business is one of the highest producers of sausage rolls in Bandar Lampung. The data of this research are primary data and secondary data, collected in March– April 2019. The first objective is analyzed by using the Hayami method, the second objective is analyzed using the Variable Costing method, and the third objective was analyzed by adding the total non-production cost and the cost of production per month. The results of the research showed that the highest added value was come from the cheesy sausage rolls while the lowest was from potato sausage rolls. All variants have positive added values and were feasible to be produced. The average cost of a noodle sausage roll production Rp962.85, a soya sausage roll Rp1,926.86, a cheesy sausage roll Rp1,768.44, a potato sausage roll Rp2,182.56 and a spicy sausage roll Rp1,982.22. The selling price of a noodle sausage roll Rp1,439.95, a soya sausage roll Rp5,180.52, a cheesy sausage roll Rp4,216.63, a potato sausage roll Rp6,907.81 and a spicy sausage roll Rp4,447.20.Key word: added value, cost of production and sausage rolls.